2013
DOI: 10.1002/hlca.201200526
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Convenient Synthesis of α,β‐Unsaturated Esters and Ketones via Aldol‐Adduct Elimination

Abstract: Various fluorinated 3‐oxo ester/1,3‐diketones were reacted with carbonyl compounds, in presence of piperidine and under microwave irradiation, to afford (E)‐α,β‐unsaturated esters and ketones in good yields. The systematic study reveals that the reaction proceeded through the formation of aldol adduct. The method provides a new and simple way for C,C bond formations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…For the aldol condensation step, activation of nucleophile is important, and alcohol firstly formed after the nucleophilic attack. It was reported that piperidine as a base in the reaction system is necessary to promote the following elimination reaction ,. Surface basic sites of LDH might play the similar role to accelerate the reaction in the present system.…”
Section: Resultsmentioning
confidence: 99%
“…For the aldol condensation step, activation of nucleophile is important, and alcohol firstly formed after the nucleophilic attack. It was reported that piperidine as a base in the reaction system is necessary to promote the following elimination reaction ,. Surface basic sites of LDH might play the similar role to accelerate the reaction in the present system.…”
Section: Resultsmentioning
confidence: 99%
“…Our research focused on the synthesis of biologically active heterocyclic compounds, and feasible reactions of carbonyl compounds/salicylaldehydes with 3-oxobutanoates bearing chloro or trifluoro substituents. In this context, we studied the reactivity of carbonyl compounds with ethyl 4,4,4-trifluoro-3-oxo­butanoate using piperidine in CH 2 Cl 2 at room temperature to provide a series of ( E )-α,β-unsaturated esters and ketones . Next, we studied the reactivity of various salicylaldehydes with ethyl 4-chloro-3-oxobutanoate using piperidine to provide 2 H -chromenes, interim these derivatives were successfully converted to corresponding 2,3-dihydro­benzoxepine-4-carboxylates .…”
mentioning
confidence: 99%